General mathematical formulation of scattering processes in atom-diatomic collisions in the RmatReact methodology - McKemmish, Laura K; Tennyson, Jonathan (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2019)
Accurately modelling cold and ultracold reactive collisions occurring over deep potential wells, such as [Formula: see text], requires the development of new theoretical and computational methodologies. One potentially useful framework is the R-matrix method adopted widely for electron-molecule collisions which has more recently been applied to non-reactive heavy-particle collisions such as Ar-Ar. The existing treatment of non-reactive elastic and inelastic scattering needs to be substantially extended to enable modelling of reactive collisions: this is the subject of this paper. Herein, we develop the general mathematical formulation for non-reactive elastic and inelastic scattering, photoassociation, photodissociation, charge exchange and reactive scattering using the R-matrix method. Of particular note is that the inner region, of central importance to calculable R-matrix methodologies, must be finite in all scattering coordinates rather than a single scattering coordinate as for non-reactive scattering. This article is part of a discussion meeting issue 'Advances in hydrogen molecular ions: H , H and beyond'.